A prototype for driving school instructor timetabling using case-based heuristics selection algorithm / CT Munnirah Niesha Mohd Shafee - Mohd Shafee, CT Munnirah Niesha (2010)
Timetabling problems are present in all type of environment. This project is concern with problem constructing timetable for driving school instructor. Driving school instructor timetabling problem regards the weekly scheduling for all the student in driving school. The problem consists in assigning student and the instructor to the time period in such a way that not more than one student involved in one session and other constraints are satisfied. The specification with both hard constraints which must be satisfied and soft constraint which should satisfied. This problem can be solved using Case-Based Heuristics Selection approaches. Then the project continues to find algorithm to be applied to generate a clash-free timetable. A prototype for driving school instructor timetabling environment will be determined followed by some experimental results.